2012
DOI: 10.1104/pp.112.205476
|View full text |Cite
|
Sign up to set email alerts
|

Differential Control of Ethylene Responses byGREEN-RIPEandGREEN-RIPE LIKE1Provides Evidence for Distinct Ethylene Signaling Modules in Tomato    

Abstract: The factors that mediate specific responses to the plant hormone ethylene are not fully defined. In particular, it is not known how signaling at the receptor complex can control distinct subsets of ethylene responses. Mutations at the Green-ripe (Gr) and reversion to ethylene sensitivity1 (rte1) loci, which encode homologous proteins of unknown function, influence ethylene responses in tomato (Solanum lycopersicum) and Arabidopsis (Arabidopsis thaliana), respectively. In Arabidopsis, AtRTE1 is required for fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 78 publications
3
27
0
Order By: Relevance
“…Previously, phylogenetic analysis suggested that members of the RTE1 gene family from different species form two clades, AtRTE1/SlGR and AtRTH/SIGRL2 (Barry and Giovannoni, 2006;Ma et al, 2012). The AtRTE1/SlGR clade consists of the RTE1 homologs that regulate ethylene signal transduction, such as Arabidopsis RTE1, tomato GR and GRL1, and rice RTH1 (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, phylogenetic analysis suggested that members of the RTE1 gene family from different species form two clades, AtRTE1/SlGR and AtRTH/SIGRL2 (Barry and Giovannoni, 2006;Ma et al, 2012). The AtRTE1/SlGR clade consists of the RTE1 homologs that regulate ethylene signal transduction, such as Arabidopsis RTE1, tomato GR and GRL1, and rice RTH1 (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The AtRTE1/SlGR clade consists of the RTE1 homologs that regulate ethylene signal transduction, such as Arabidopsis RTE1, tomato GR and GRL1, and rice RTH1 (Zhang et al, 2012). The AtRTH/ SIGRL2 clade includes AtRTH and SlGRL2, which have no apparent role in ethylene signaling (Resnick et al, 2006;Ma et al, 2012); petunia PhGRL2, which was proposed to regulate ethylene biosynthesis (Tan et al, 2014), and rice RTH3, whose function is unknown (Zhang et al, 2012). ZmRTL4 is more closely related to the AtRTH/SlGRL2 clade, while ZmRTL2 apparently belongs to the AtRTE1/SlGR clade (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations